Le valutazioni economiche in Italia: una revisione sistematica della letteratura esistente - Garattini, L.; Clemente, R.; De Compadri, P.; Denti, C. (Farmeconomia. Health economics and therapeutic pathways, 2001)
Aim of this paper is to provide some systematic information about Economic Evaluation studies published on national and international journals by Italian authors. All studies are in Italian or English language and published between 1994 and 2000. The main source is the CESAV database, according to these keywords: “Economic Evaluation”, “Cost-Benefit Analysis”, “Cost-Efficacy Analysis”, “Cost-Utility Analysis”, Cost of Illness” and “Italy”. The study investigated the following variables: methods of analysis, illness, kind of therapy, source of data on efficacy, modelling, source of data on health resources, source of data on unit cost, type of costs, sensitivity analysis. A comparison with the main international reviews (“The U .K. NHS Economic Evaluation Database” and “The Health Economic Evaluation Database”) showed that the approach to the Economic Evaluation in Italy is consistent to the European model, even though the number of studies is still less than in other States.